IMPLEMENTASI NILAI-NILAI GAYA KEPEMIMPINAN SITUASIONAL DALAM FILM “SANG KYAI" - Muhammad Raihan Al Farisi, Muhammad Raihan Al Farisi (DIGICOM : Jurnal Komunikasi dan Media, 2024)
This study aims to analyze the implementation of situational leadership values depicted in the film Sang Kiai, which features K.H. Hasyim Asy'ari as a flexible and responsive leader facing challenges. The research employs a qualitative method, gathering data from relevant literature and analyzing scenes from the film that illustrate his leadership style. K.H. Hasyim Asy'ari demonstrates the ability to adapt to situations, both in confronting colonialism and in guiding his students, applying a leadership style characterized by decisiveness, emotional support, and participation in decision-making. The findings emphasize the importance of integrating religious values and nationalism in leadership, showing that K.H. Hasyim Asy'ari's application of situational leadership not only enhances leadership effectiveness but also remains relevant in modern contexts where leaders must navigate continuously changing challenges. This study provides insights into how an adaptive leadership approach can be implemented to achieve common goals across various fields.